Теоретичний аналіз процесів сумісного вилучення органічних забруднень і азоту при очистці стічних вод на затоплених фільтрах - Ігнатенко, Д.А. (Екологічна безпека та природокористування, 2012)
The simplified models of the simultaneously purification of the waste waters from the organic pollutions and the nitroge on the ponded filters at the conditions of the enough supply of the biooxidation processes by the oxygen on the base of the general mathematic model are gropesed for furthe realization in practical calculations. The recommendations which allow to evaluate the influence of the different factors on the velocity (kinetics) of the reactions and the mass transfer processes are presented.